2018
DOI: 10.4269/ajtmh.18-0082
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assurance and Quality Control in the Global Trachoma Mapping Project

Abstract: Abstract.In collaboration with the health ministries that we serve and other partners, we set out to complete the multiple-country Global Trachoma Mapping Project. To maximize the accuracy and reliability of its outputs, we needed in-built, practical mechanisms for quality assurance and quality control. This article describes how those mechanisms were created and deployed. Using expert opinion, computer simulation, working groups, field trials, progressively accumulated in-project experience, and external eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 21 publications
1
58
0
1
Order By: Relevance
“…The survey methodology used was based on that of the GTMP, 34 as modified and refined by Tropical Data (www.tropicaldata.org). 35,36 Our approaches were consistent with WHO recommendations for trachoma prevalence surveys. 32,37…”
Section: Methodssupporting
confidence: 68%
See 1 more Smart Citation
“…The survey methodology used was based on that of the GTMP, 34 as modified and refined by Tropical Data (www.tropicaldata.org). 35,36 Our approaches were consistent with WHO recommendations for trachoma prevalence surveys. 32,37…”
Section: Methodssupporting
confidence: 68%
“…Later analyses suggested that the use of ITM carried some risk of district misclassification, 29 and in the present work, we reverted to the use of cluster-sampled, populationbased surveys. Our highly standardized, qualitycontrolled and quality-assured 36 methodologies are considered to provide highly reliable data 53 ; we believe, on this basis, that the prevalence estimates generated here supersede those produced in 2012.…”
Section: Discussionmentioning
confidence: 83%
“…Standard GTMP approaches 28,29 were used for data cleaning, analysis, health ministry review, and approval. In the first 23 completed EUs, lacking information on the presence or absence of TS in eyes with trichiasis, we calculated the prevalence of "any trichiasis"; for the last 19 completed EUs, we calculated the prevalence of both any trichiasis and "trichiasis+TS", defined here as the presence of both trichiasis and TS (or the inability of the examiner to evert the lid to look for TS, presumed to be due to dense scarring) in the same eye.…”
Section: Discussionmentioning
confidence: 99%
“…Completion of the survey was a credit to the field teams, who negotiated the terrain without complaint and returned data of high quality. 28,37 There was, however, one particular shortcoming in our survey. Because of access issues and the spatial distribution of households, as noted in the Methods section above, it was not possible to include 30 households in each village.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we employed the momentum, 18,27 systems 19,28 and funding 29 of the GTMP to investigate whether trachoma was a public health problem in an area felt to be the most at-risk part of the Republic of the Congo, a hitherto-unsurveyed country. This survey was set up as the epidemiological equivalent of a canary in the mine, with the understanding that finding trachoma at levels indicative of a public health problem here would prompt further trachoma surveys in surrounding health districts, 3,4 and potentially further afield.…”
Section: Discussionmentioning
confidence: 99%